IMPROVING THE STUDENTSâ€™ SPEAKING SKILL BY USING COMMUNICATION GAMES - Yulius Harry Widodo; Muhyiddin Aziz (Humaniora Scientia, 2017)
Teaching language consists of some aspects as the important part of transfering the knowledge and skill such as the skill of the lecturers to manage the process of teaching and learning as they play an important roles, choosing the methods or strategies, and designing the goal of the study. All their targets are based on how well they colaborate the methods and designs through the experiences and knowledge they have during the process of teaching and learning. Communication Games was chosen to know the effectiveness, advantages, disadvantages, streghts, and weaknessesÂ  in improving the speaking skill of the second semester students of English Department of Madiun State Polytechnic. The qualitative and quantitative data were used in this research. Qualitative data were taken from the scores of the pre-test and all cycles. The qauntitative data were taken through the observation, interview, and questionnaire. Based on the discussions and conclusions, communication games is recomended to improve the speaking skill of the second semester students of English Department of Madiun State Polytechni.